Sonographic Demonstration of Intracranial Hemorrhage in a Fetus with Hydrops Fetalis due to Rh Alloimmunization after Intrauterine Intravascular Transfusion: A Case Report and Review of the Literature - Rauf Melekoglu; Ebru Celik; Hasim Kural (Case Reports in Obstetrics and Gynecology)
Intrauterine transfusion is the most common and successful intrauterine procedure for the treatment of fetal anemia due to red cell alloimmunization. Fetal intracranial hemorrhage is a very rare complication of intrauterine transfusion in patients with Rh(D) alloimmunization and it has been demonstrated only in a few case reports in the literature. Herein, we described a case of grade IV intraventricular hemorrhage that was diagnosed following the first intrauterine transfusion and reviewed the literature about the fetal intracranial hemorrhage that occurred after intrauterine intravascular transfusion procedure.